Infiltration of Th1 and Th17 cells and activation of microglia in the CNS during the course of experimental autoimmune encephalomyelitis - MILLS, KINGSTON; LYNCH, MARINA; LALOR, STEPHEN (My University, 2010)
Experimental autoimmune encephalomyelitis (EAE) is a mouse model for multiple sclerosis, where disease is mediated by autoantigen-specific T cells. Although there is evidence linking CD4+ T cells that secrete IL-17, termed Th17 cells, and IFN-?-secreting Th1 cells with the pathogenesis of EAE, the precise contribution of these T cell subtypes or their associated cytokines is still unclear. We have investigated the infiltration of CD4+ T cells that secrete IFN-?, IL-17 or both cytokines into CNS during development of EAE and have examined the role of T cells in microglial activation. Our findings demonstrate that Th17 cells and CD4+ T cells that produce both IFN-? and IL-17, which we have called Th1/Th17 cells, infiltrate the brain prior to the development of clinical symptoms of EAE and that this coincides with activation of CD11b+ microglia and local production of IL-1?, TNF-? and IL-6 in the CNS. In contrast, significant infiltration of Th1 cells was only detected after the development of clinical disease. Co-culture experiments, using mixed glia and MOG-specific T cells, revealed that T cells that secreted IFN-? and IL-17 were potent activators of pro-inflammatory cytokines but T cells that secrete IFN-?, but not IL-17, were less effective. In contrast both Th1 and Th1/Th17 cells enhanced MHC class II and co-stimulatory molecule expression on microglia. Our findings suggest that T cells which secrete IL-17 or IL-17 and IFN-? infiltrate the CNS prior to the onset of clinical symptoms of EAE, where they may mediate CNS inflammation, in part, through microglial activation.
PUBLISHED
Keywords: Experimental autoimmune encephalomyelitis; Th1 cells; Th17 cells; IFN-?; IL-17; Microglia; inflammatory cytokine; multiple sclerosis; Immunology, Inflammation & Infection; Neuroscience